“Wenn dunkel mir ist der Sinn,/Den Kunst und Sinnen hat Schmerzen/Gekostet von Anbeginn” (“When Dark Are My Mind and Heart/Which Paid from the Beginning/In Grief for Thought and Art”): Hölderlin in the “Hölderlin Tower”—Contemporary and Modern Diagnoses of His Illness, and Literary (Self-)Therapy - Gabriele von Bassermann-Jordan (Humanities)
In 1802, Friedrich Hölderlin experienced his first mental breakdown, which was followed by a second one in 1805. On 15th September 1806, he was admitted to the clinic of Johann Heinrich Ferdinand von Autenrieth in Tübingen who addressed Hölderlin’s illness as “madness” (“Wahnsinn”). On 3rd May 1807, the poet was discharged as “incurable” (“unheilbar”). Until his death on 7th June 1843, he was cared for by the carpenter Ernst Zimmer. From the period between 1807 and 1843, 50 poems by Hölderlin have been preserved, in German studies known as the “Turmdichtung” (“tower poetry”). These poems have long been relegated to the margins of scholarly research. In my essay, I will discuss the modern and contemporary diagnoses, as well as Hölderlin’s literary (self-) therapy of his illness. I am suggesting that Hölderlin’s tower poetry contains a thera-peutic–poetic concept that is intended to serve the treatment of his illness.